2017
DOI: 10.1002/mds.26921
|View full text |Cite
|
Sign up to set email alerts
|

Manual MRI morphometry in Parkinsonian syndromes

Abstract: The midsagittal midbrain area most reliably identified PSP, the midsagittal pons area MSA-cerebellar. The midbrain/pons area ratio differentiated MSA-cerebellar and PSP better than the magnetic resonance-Parkinson index. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 22 publications
5
106
2
Order By: Relevance
“…Voxel-based morphometry (VBM), an operator-independent automated method, can detect focal volume differences between 2 or more groups based on study-specific templates (Ashburner et al, 2000). Studies using this approach confirmed previous ROI-based volumetric studies suggesting basal ganglia, infratentorial as well as cortical volume loss in MSA patients (Minnerop et al, 2007; Moller et al, 2017; Specht et al, 2003; Tzarouchi et al, 2010). Moreover, specific longitudinal changes in MSA (early atrophy of basal ganglia followed by late cortical atrophy) have been identified with this technique (Brenneis et al, 2007).…”
Section: Brain and Cardiac Neuroimagingsupporting
confidence: 83%
“…Voxel-based morphometry (VBM), an operator-independent automated method, can detect focal volume differences between 2 or more groups based on study-specific templates (Ashburner et al, 2000). Studies using this approach confirmed previous ROI-based volumetric studies suggesting basal ganglia, infratentorial as well as cortical volume loss in MSA patients (Minnerop et al, 2007; Moller et al, 2017; Specht et al, 2003; Tzarouchi et al, 2010). Moreover, specific longitudinal changes in MSA (early atrophy of basal ganglia followed by late cortical atrophy) have been identified with this technique (Brenneis et al, 2007).…”
Section: Brain and Cardiac Neuroimagingsupporting
confidence: 83%
“…Measurements of these regions, and ratios thereof (e.g. midbrain-pons ratio, MR-Parkinson-index) proofed therefore very helpful as markers for the cross-sectional differential diagnosis of Parkinson syndromes, 24,25 however, only limited data addressed the utility of these ratios as progression measurement. 8 …”
Section: Discussionmentioning
confidence: 99%
“…In the midsagittal planes, several previous studies suggested the midbrain area and midbrain tegmentum area as reliable markers of atrophy in PSP. 24,25 For comparison, the midsagittal areas of other structures (corpus callosum, pons and pars basilaris of pons, medulla oblongata, cerebellar vermis) have also been determined. All cross-sectional results of ABV were ICV-corrected and normalized to the mean ICV of the whole study population.…”
Section: Methodsmentioning
confidence: 99%
“…HC)m d /p d -ratioSe 86 (PSP)Sp 100 (vs. PD, MSA. HC)Kim et al (2015)PD 82/PSP 293.0 Tm d d  and m a /p a ratio discriminated PSP from PD with similar discriminatory powerMRPI showed lower discriminatory powerm d Se 86 (PSP)Sp 54AUC = 0.76m a /p a ratio (Cosottini method) (Cosottini et al 2007)Se 62 (PSP)Sp 76AUC = 0.75m a /p a ratio (Oba method) (Oba et al 2005)Se 72 (PSP)Sp 64AUC = 0.75MRPISe 93 (PSP-RS)Sp 43AUC = 0.69Moller et al (2017)PD 204/PSP 106/MSA-C 21/MSA-P 60/HC 731.5 and 3.0 T↓ m a in PSP vs. all other groups↓ p a in MSA-C, MSA-P, and PSP vs. PD and HC.↓ m a /p a in PSP vs. all other groups↑ m a /p a in MSA-C and MSA-P vs. PD and PSPm a AUC = 0.90 (PSP vs. PD)Se 75, Sp 82, AUC = 0.85 (PSP vs. MSA-P)m a /p a Se 76, Sp 80, AUC = 0.84 (PSP vs. PD)Se 76, Sp 80, AUC = 0.89 (PSP vs. MSA-P)MRPISe 64, Sp 64, AUC = 0.75 (PSP vs. PD)Se 73, Sp 60, AUC = 0.80 (PSP vs. MSA-P)Automated methods for quantitative MRI analysis Huppertz et al (2016)PD 204, PSP 106, MSA-C 21, MSA-P 601.5 and 3.0 TFully automated brain volumetry combined with SVM classification allowed for automated differentiation on single-patient levelVolume changes of midbrain, basal ganglia, and cerebellar peduncles had the largest relevance for classificationAtlas-based voxel-based volumetry combined with SVM classificationClassifications between the groups resulted in balanced diagnostic accuracies ≥80% Scherfler et al (2016)PSP 30/MSA 40/PD 40 of whom 40 presented with a clinically uncertain parkinsonism  Data were split into a training ( n  = 72) and a test set ( n  = 38)1.5 TVolume segmentation of subcortical brain regions followed by a machine-learning method-derived classification algorithm (i.e. C4.5 decision tree algorithm)Most discriminative regions include the volume of the midbrain, followed by cerebellar GM and putamenDiagnostic accuracy of the fully automated method for quantitative MRI analysis was 97% for the separation of PD vs. MSA or PSP, by contrast to the clinical diagnostic accuracy of 63% based on validated clinical consensus criteria at the time of MRI…”
Section: Exclusion Of Alternative Diagnosesmentioning
confidence: 99%